CRM-Change Management: The Role Of Training In Successful CRM Implementation - Koohestani, Ali (2006)
This research focuses on training as an aspect of change management process, aims to analyze and investigate the role of training along the change management process while implementing CRM solutions. In this regard, identification of necessary changes, required trainings, types and contents of training programs in detail are considered and discussed.